Flexible scope for ISO15189 accreditation requires harmonization of scope specificity - Thelen, Marc H. M. (Journal of Laboratory and Precision Medicine; Vol 2 (October 2017): Journal of Laboratory and Precision Medicine, 2017)
ISO15189 has become the standard for quality management in laboratory medicine and its accreditation. To specify which activities are part of the accreditation a scope of accreditation is mandatory. A scope may be fixed with every individual activity listed or flexible with grouping of obviously coherent activities. Although European Accreditation (EA) promotes the flexible approach, in most countries the majority of the scopes is fixed. The European Federation for Clinical Chemistry and Laboratory Medicine (EFLM) has published a guidance document to stimulate the use of a flexible scope. This guidance also advises to define the right degree of specificity of the scope based on a risk analysis performed in cooperation between national accreditation body and the scientific societies involved. The guidance was based on a successful, consensus based approach in the Netherlands where it led to the introduction of the definition of a source scope for every scientific society involved in laboratory medicine and adoption of the flexible scope by all laboratories that have made the transition for the former CCKL towards ISO15189 accreditation. So far, over 50% of all Dutch medical laboratories have made that transition and definition of scope has never been an issue in these transitions. Since the definition of the flexible source scope for each society in the Netherlands in 2014 there has been a trend to add specificity. Because adding specificity makes a particular working field more distinguishable from another, addition of specificity leads to a chain reaction of such additions in the source scope of societies. This might endanger the intentions of the flexible scope if increasing specificity would eventually would lead to an almost fixed scope. A harmonized approach in overlapping working areas of the different scientific societies is needed to find the optimal balance in scope granularity between specificity and flexibility.